Zoopolis : a political theory of animal rights - Donaldson, Sue.; Kymlicka, Will, 1962- (Oxford ; New York : Oxford University Press, 2013)
Zoopolis offers a new agenda for the theory and practice of animal rights. Most animal rights theory focuses on the intrinsic capacities or interests of animals, and the moral status and moral rights that these intrinsic characteristics give rise to. Zoopolis shifts the debate from the real of moral theory and applied ethics to the realm of political theory, focusing on the relational obligations that arise from the varied ways that animals relate to human societies and institutions. Building on recent developments in the political theory of group-differentiated citizenship, Zoopolis introduces us to the genuine "political animal." It argues that different types of animals stand in different relationships to human political communities. Domesticated animals should be seen as full members of human-animal mixed communities, participating in the cooperative project of shared citizenship. Wilderness animals, by contrast, form their own sovereign communities entitled to protection against colonization, invasion, domination, and other threats to self-determination. "Liminal" animals who are wild but live in the midst of human settlement (such as crows or raccoons) should be seen as "denizens", residents of our societies, but not fully included in rights and responsibilities of citizenship. To all of these animals we owe respect for their basic inviolable rights, but we inevitably and appropriately have very different relations with them, with different types of obligations. Humans and animals are inextricably bound in a complex web of relationships, and Zoopolis offers an original and profoundly affirmative vision of how to ground this complex web of relations on principles of justice and compassion.
Introduction -- Universal basic rights for animals -- Extending animal rights via citizenship theory -- Domesticated animals within animal rights theory -- Domesticated animal citizens -- Wild animal sovereignty -- Liminal animal denizens -- Conclusion.
boek
Keywords: Animal rights; Human-animal relationships -- Moral and ethical aspects